Rabies transmitted from vampires to cattle: An overview - Diego Soler-Tovar; Luis E. Escobar (PLoS ONE, 2025)
Rabies is a zoonotic infectious disease of global distribution that impacts human and animal health. In rural Latin America, rabies negatively impacts food security and the economy due to losses in livestock production. The common vampire bat, Desmodus rotundus, is the main reservoir and transmitter of rabies virus (RABV) to domestic animals in Latin America. Desmodus rotundus RABV is known to impact the cattle industry, from small farmers to large corporations. We assessed the main patterns of rabies in cattle attributed to D. rotundus RABV across Latin America. Epidemiological data on rabies from Latin America were collected from the Pan American Health Organization spanning the 1970–2023 period. Analyses revealed an average of 450 outbreaks annually for the countries where D. rotundus is distributed, with at least 6 animals dying in each outbreak. Brazil, Colombia, Peru, and Mexico were the Latin American countries with the highest number of rabies outbreaks during the study period and are the most affected countries in recent years. Findings suggest a re-emergence of bat-borne rabies in the region with more outbreaks reported in recent years, especially during the 2003–2020 period. Rabies outbreaks in cattle in the 2000–2020 period were significantly more frequent than in previous decades, with an increase in cross-species transmission after 2002. The size of outbreaks, however, was smaller in recent years, involving lower cattle mortality. Peru, El Salvador, and Brazil showed a strong association (R = 0.73, p = 0.01) between rabies incidence in D. rotundus (rates per million humans: 1.61, 0.94, and 1.09, respectively) and rabies outbreaks in cattle (rates per million cattle: 465.85, 351.01, and 48.22, respectively). A sustained, standardized, and widespread monitoring of D. rotundus demography and health could serve to inform an early warning system for the early detection of RABV and other bat-borne pathogens in Latin America. Current data can be used to forecast when, where, and in which intensity RABV outbreaks are more likely to occur in subtropical and tropical Latin America. A decrease in the size of outbreaks could suggest that strategies for epidemic management (e.g., education, early diagnosis, vaccination) have been effective. The increase in the number of outbreaks could suggest that the factors facilitating cross-species transmission could be on the rise.